It worked in China, so why not in Africa? The political economy challenge of special economic zones - Thomas Farole; Lotta Moberg (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
African countries have sought to replicate the success of East Asia by implementing special economic zones. Despite decades of international experience, there remains no blueprint for successful special economic zone policies, and the majority of special economic zones fall well below expectations. We argue this is largely due to flaws in the political economy of special economic zone schemes, which prevent replication of 'best practice' in special economic zone development and management. We propose a 'robust political economy' framework that divides political economy problems into those of inadequate knowledge and distorted incentives. We use it to explain the problems with African special economic zones and to suggest possible solutions.
Keywords: F13; F23; F59; F63; O24; P48; 330; Special Economic Zones; Sub-Saharan Africa; foreign direct investment; political economy; industrial policy